Potency of Bentonite and Pelawan Wood Active Charcoal as Virgin Coconut Oil (VCO) Purity Improvements Through Free Fatty Acid Binding - Utami, Sri Risky; Lidya, Lidya; Afrilia, Mega; Mahardika, Robby Gus (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
Virgin Coconut Oil (VCO) is pure coconut oil produced from fresh coconuts and does not contain additional chemicals. VCO has a high lauric acid content which acts as an antibiotic, namely antiviral, antibacterial and antiprotozoal so that VCO can increase the human body's resistance to disease or viruses. Free fatty acid (FFA) levels will significantly affect the quality of VCO. The requirement for maximum fatty acid content in VCO to be suitable for consumption is 0.2%. One of the efforts to reduce the free fatty acid levels of VCO is to use adsorbents such as activated charcoal and bentonite. This study aims to determine the effect of bentonite and activated charcoal of pelawan wood (Tristaniopsis merguensis) enhancers of VCO purity. The results showed that the best reduction in free fatty acids was using bentonite and activated charcoal of wood-furnaced pelawan, which was 0.265, while the best turbidity test result was 0.193.